Effects of tree sex, maturity, local abiotic, and biotic neighborhoods on the growth of a subtropical dioecious tree species Diospyros morrisiana. Issue 2 (18th January 2023) - He, Qing; Queenborough, Simon A.; Zhang, Yonghua; Wang, Weitao; Li, Buhang; Zhao, Kangning; Luo, Wenqi; Tang, Hui; Lin, Wei; Chu, Chengjin
Abstract: Premise: Understanding the drivers of the growth in long‐lived woody trees is the key to predicting their responses to and maintaining their populations under global change. However, the role of tree sex and differential investment to reproduction are often not considered in models of individual tree growth, despite many gymnosperm and angiosperm species having separate male and female sexes. Thus, better models of tree growth should include tree sex and life stage along with the abiotic and biotic neighborhoods. Methods: We used a sex‐specific molecular marker to determine the sex of 2188 individual trees >1 cm DBH of the dioecious tree species Diospyros morrisiana in a 50‐ha subtropical forest plot in China. We used long‐term census data from about 300, 000 trees, together with 625 soil samples and 2352 hemispherical photographs to characterize the spatially explicit biotic and abiotic neighborhoods. Results: We found a male‐biased effective sex ratio and a female‐biased overall population sex ratio of D. morrisiana . No sex spatial segregation was detected for the overall population, mature, or immature trees. Immature trees grew faster than mature trees and females grew slower than males. Further, conspecific neighbors significantly decreased tree growth, while the abiotic neighborhood showed no significant effect. Conclusions: Our findings suggest that variation in resource allocation patterns within and across individual trees of different sexes and life‐history stages should be more widely accounted for in models of tree growth. In addition, our study highlights the importance of sex‐specific molecular markers for studying populations of long‐lived dioecious tree species.